Nalbuphine as an adjuvant to bupivacaine in ultrasound-guided brachial plexus blockade: A meta-analysis of randomized and controlled trials - Rajesh Kumar,; Jaiswal, Apoorva (Asian Journal of Medical Sciences, 2024)
The brachial plexus block is a flexible and reliable regional anesthetic method with a wide range of applications. In this study, we aim to determine whether nalbuphine in combination with the local anesthetic bupivacaine could increase the efficacy and duration of analgesia during ultrasound-guided blockade of the brachial plexus. Seven randomized and controlled trials involving 416 patients were included after searching PubMed, Google, and Web of Science. Results of the studies were then retrieved and effect sizes were calculated using Review Manager 5. Duration of analgesia was significant heterogeneity between studies (P<0.00001, I2=96%). A random-effects model was used, and there was significant heterogeneity between studies in the duration of analgesia. A significant difference was found between groups (standard mean difference [MD] 6.27, confidence interval [CI] [4.40–8.60], P<0.001). Duration of motor block was also significant heterogeneity between studies (P<0.00001, I2=98%). A random-effects model was used, and there was significant heterogeneity between studies in the duration of motor block. A significant difference was found between groups (standard MD 6.27, CI [4.01–8.54], P<0.001). In supraclavicular brachial plexus blockade, the duration of analgesia and the duration of motor blockade can be prolonged using nalbuphine as an adjuvant with bupivacaine.